Fenomenologia, Política e o Pensamento de Jan Patočka: reverberações latino-americanas - Marandola Jr., Eduardo; Batista, Gustavo Silvano; Cordova, Vitor Sartori (Pensando - Revista de Filosofia, 2023)
Editorial Dossiê Jan Patočka